Prognostic Impact of the Presence of Barrett's Esophagus and Intestinal Metaplasia on Esophageal Adenocarcinoma Survival. Issue 4 (December 2022) - Kolb, Jennifer M.; Fox, Charlie; Friedman, Chloe; Scott, Frank I.; Han, Samuel; Marsh, Megan; McCarter, Martin; Kaplan, Jeffrey; Lieu, Christopher H.; Gleisner, Ana; Katzka, David A.; Wani, Sachin
Background/Aims: Barrett's esophagus (BE), defined by the presence of intestinal metaplasia (IM) on histology, is thought to be the only identifiable precursor lesion for esophageal adenocarcinoma (EAC). Recent studies have suggested the possibility of an alternate, non-IM associated EAC that is a more aggressive form of EAC with worse survival. Among EAC patients, we aimed to compare survival of patients with and without IM at the time of diagnosis. Methods: This was a retrospective cohort study of all patients with histologic confirmed EAC evaluated at a tertiary care center from 2013 to 2019. Cases were categorized according to the presence or absence of IM on histologic specimens (Group I—IM-EAC and Group II—non-IM-EAC). We compared demographic characteristics, clinical stage, therapy, and survival between the 2 groups using the Chi-square and ANOVA tests (for categorical and continuous variables, respectively). We used Cox proportional hazards regression to determine the association of IM with overall survival, adjusting for sex, age at diagnosis, tumor location, histologic grade, and clinical stage. Results: A total of 475 patients were included in this analysis (mean age 64.8 years [SD 10.8], 89% white) and 109 (23.0%) had no evidence of IM. Compared with IM-EAC (Group I), individuals in the non-IM-EAC group were younger ( P  = .01) and had a greater proportion of patients diagnosed with advanced disease (49.5 vs 20.2% for stage 4, P  < .001). These patients were less likely to undergo endoscopic therapy alone (0.92% vs 29.78%, P  < .001) or surgery alone (0 vs 9.84%, P  = .001). On multivariable analysis, the presence of IM-EAC was associated with improved overall survival compared to non-IM-EAC (HR 0.69, 95% CI 0.49-0.96). Additional factors associated with poor survival was increasing stage of diagnosis (HR 6.49: 95% CI 3.77-11.15 for stage 4, HR 2.19: 95% CI 1.25-3.84 for stage 3, HR 2.04: 95% CI 0.98-4.25 for stage 2 compared to stage 1) and more advanced histologic stage (HR 2.00, 95% CI 1.26-3.19) for poorly/undifferentiated compared to well differentiated). Conclusions: EAC without the presence of IM on histology was associated with worse survival compared to those with IM. Future prospective studies with detailed molecular sequencing are required to clarify if 2 separate phenotypes of EAC exist (IM-EAC and non-IM-EAC). If confirmed, this may have significant implications for screening and management strategies.